Metal Stents for the Management of Massive Hemobilia in Patients with Hilum-Involving Cholangiocarcinoma Receiving Multi-Regimen Chemotherapy - Seung Yeon Lee; Min Je Sung; Suk Pyo Shin; Hong Jae Chon; Beodeul Kang; Kwang Hyun Ko; Mamoru Takenaka; Chang-Il Kwon (Gut and Liver)
Recent clinical outcomes of multi-regimen chemotherapy in patients with cholangiocarcinoma (CCC) have shown benefits in terms of overall survival. However, repeated endoscopic biliary drainage (EBD) and serious adverse events negatively affect prolongation of the survival period. The aim of this study was to investigate the prevalence of massive hemobilia and the outcomes of its management with fully covered self-expandable metal stents (FC-SEMSs) in patients with hilum-involving CCC receiving multi-regimen chemotherapy. The methods and effects of FC-SEMS placement were retrospectively investigated following the occurrence of massive hemobilia during EBD. A total of 356 patients with CCC received multi-regimen chemotherapy. Among them, 181 patients had hilar invasion, and seven patients (3.9%) developed massive hemobilia during repeated EBD using removable stents. In all cases, the tumor encased the right hepatic artery. In six patients (85.7%), hemostasis was immediately and completely achieved by inserting one or two FC-SEMSs proximal to the hilar invasion area. Therefore, if the tumor encases the right hepatic artery, massive hemobilia is likely to occur during multi-regimen chemotherapy. Thus, prompt placement of a FC-SEMS would be an effective treatment option for massive hemobilia in patients with hilum-involving CCC.